2019
DOI: 10.29333/iji.2019.12114a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Types of Peer Feedback Provision on EFL Students’ Writing Performance

Abstract: Writing in English is often claimed as the most complex skills compared to the other three skills. Due to its complexity, feedback is seen to be an important part in writing process since it can lead to the students' better writing performance. It has been a consensus that teacher feedback is not practical to be given in a class with a big number of students; thus, this challenges peer feedback to be implemented in the writing classroom. While there are studies showing that peer feedback is effective to enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 25 publications
4
34
0
1
Order By: Relevance
“…The pre-test and post-test results were also congruent with the findings of Kuyyogsuy (2019) who reported statistically significant differences between pupils' mean scores for writing pre-test and post-test in examining the impacts of peer feedback on students' English writing skills. Additionally, this corresponded to the findings of Kusumaningrum, Cahyono, and Prayogo (2019) who reported that pupils could enhance their written tasks by correcting peers' work. They showed that pupils could develop efficacy in writing through peer feedback.…”
Section: Is There Any Significant Difference In Writing Performance Mean Scores For Experimental and Control Groups Before And After Peersupporting
confidence: 87%
“…The pre-test and post-test results were also congruent with the findings of Kuyyogsuy (2019) who reported statistically significant differences between pupils' mean scores for writing pre-test and post-test in examining the impacts of peer feedback on students' English writing skills. Additionally, this corresponded to the findings of Kusumaningrum, Cahyono, and Prayogo (2019) who reported that pupils could enhance their written tasks by correcting peers' work. They showed that pupils could develop efficacy in writing through peer feedback.…”
Section: Is There Any Significant Difference In Writing Performance Mean Scores For Experimental and Control Groups Before And After Peersupporting
confidence: 87%
“…As far as L2 writing is concerned, various scholars have corroborated the usefulness of blogs for enhancing writing competencies (Armstrong & Retterer, 2008;Dizon & Thanyawatpokin, 2018;Fathi & Nourzadeh, 2019;Nguyen, 2012;among others). The effectiveness of blogs in L2 writing is usually associated to their potentials in providing the users with access to the links of other online resources, encouraging further writing practice, providing a real audience to write for, increasing cooperation, fostering autonomous learning, shaping a sense of ownership, building a sense of community, improving learner engagement, and promoting further feedback (Campbell, 2003(Campbell, , 2005Chen, 2016;Fathi & Nourzadeh, 2019;Fathi & Rahimi, 2020;Fellner & Apple, 2006;Nguyen, 2012;Kusumaningrum, Cahyono, & Prayogo, 2019;Rahimi & Fathi, 2021;.…”
Section: Introductionmentioning
confidence: 99%
“…In line with that, a study conducted by Ting & Qian (2010) also say that peer feedback will make students become more critical readers and revisers through reading others' writing critically. In line with the statement, a research study conducted by (Kusumaningrum, Cahyono, & Prayogo (2019) stated that responding to peer's writing can build the critical skills that are needed to analyze and revise one's own writing. This statement is supported by B. Y.…”
Section: Discussionmentioning
confidence: 87%